Perancangan Bahan Ajar Berbasis E-Modul Pada Mata Pelajaran Tik di SMK Zaidar Yahya - Milleni, Angria; Wahyudi, Sri (Jurnal Pendidikan Teknologi Informasi dan Vokasional, 2024)
This research aims to develop e-modules for Information and Communication Technology (ICT) subjects at Zaidar Yahya Vocational School to increase learning effectiveness. E-modules were chosen to overcome the lack of reference books and monotonous learning methods. The e-module development follows the Research and Development (R&D) method with the 4D model (Define, Design, Develop, Disseminate). The validation results show that this e-module is very valid and suitable for use, with a score of 99% from material experts and 93% from media experts. The practicality test also received a positive response from students with an acceptance rate of 87%. The e-module design uses the Canva application with bright colors and simple features to increase the attractiveness and comfort of learning. The use of Google Forms for attendance and evaluation further increases efficiency in data collection.The conclusion of this research is that the e-module developed has succeeded in overcoming the problem of lack of book references and inefficient learning methods. This e-module makes it easier for students to understand ICT material better and provides a more interesting and interactive learning experience. Therefore, this e-module is recommended as an effective alternative in supporting the learning process at Zaidar Yahya Vocational School.